GENE-33. INTEGRATED GLIOMA DIAGNOSTICS USING TARGETED NEXT-GENERATION SEQUENCING. (11th November 2019) - Petersen, Jeanette K; Boldt, Henning B; Sorensen, Mia; Dahlrot, Rikke H; Hansen, Steinbjørn; Burton, Mark; Thomassen, Mads; Kruse, Torben; Poulsen, Frantz R; Andreasen, Lotte; Hager, Henrik; Ulhøi, Benedicte P; et al.
Abstract: INTRODUCTION: Targeted next-generation sequencing (NGS) offers promising diagnostic perspectives by making it possible to detect genetic alterations with high accuracy in multiple genes as part of the daily diagnostic work-up. The importance of genetic alterations is reflected in the 2016 WHO classification of CNS tumors, where specific alterations are incorporated in the definition of certain entities. The aim of this study was to assess the diagnostic potential of a customized targeted glioma-tailored 20-gene panel to identify molecular entities of gliomas and explore their distinct mutational profiles. Moreover, the prognostic impact of molecular diagnostics was explored. METHODS: We used a setup with NGS, immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) on a series of 756 glioma from both a retro- and prospective cohort. NGS data were obtained for 347 gliomas (225 analyzed prospectively, 122 analyzed retrospectively). RESULTS: Three major clusters were identified by unsupervised hierarchial cluster analysis: 1) isocitrate dehydrogenase gene (IDH) 1 or 2 mutant astrocytomas with frequent mutations in TP53 (83%) and ATRX (69%), 2) IDH-mutant and 1p/19q-codeleted oligodendrogliomas with frequent mutations in TERT (65%) and CIC (52%), and 3) IDH-wildtype astrocytic gliomas/glioblastomas with frequent mutations in TERT (32%), PTEN (28%) and TP53 (22%). Among the IHC IDH1-R132H negative gliomas, NGS detected other IDH mutations in 16% of the cases. Moreover, rare but diagnostically important mutations such as BRAF V600E and H3F3A K27M were detected. Survival analysis of the reclassified gliomas showed a clear difference in survival between patients with WHO 2007 and 2016 diagnoses. Successful prospective NGS analyses were obtained for 98% of the gliomas in daily diagnostics. CONCLUSION: Application of NGS panel sequencing improves diagnostic accuracy and is feasible in daily diagnostics. NGS is ready to become part of standard diagnostics in the field of gliomas.